Should Islamic Banking & Financial Institutions go with General Data Protection Regulation Compliance? - Manda, Vijaya Kittu; Eskhita, Radwan (International Journal of Islamic Economics and Finance (IJIEF), 2019)
The new European Union (EU) data protection law - General Data Protection Regulation (GDPR)that is enforceable on all entities, within and outside the territory of European Union requires that follow entities dealing with private data of EU individuals should follow due procedures in regard to safe data handling and storage. This regulation is forcing all countries globally, including those in the Islamic countries to take special precautions. Islamic banks and financial institutions are key intermediaries fostering smooth foreign trade between Islamic and European countries. Lack of sufficiently strong data protection legislation in most of the Islamic countries is hampering conformity with GDPR. This leads to non-compliance and thereby paves way to heavy monetary penalties in the short-run and hurts business prospects with the European counties in the long-run, both of which are detrimental. This paper helps institutions in building frameworksby taking them through a series of compliance checks, build teamsto enforce standards, make knowledge repositories and to undertake necessary technical measures. Findings from this study can help Islamic companies in general and Islamic Banking Financial institutions in particular in meeting GDPR compliance.Finally, this paper makes some key recommendations to the Governments, Regulators, Financial Institutions, Organizations and Individuals so that they can become GDPR complaint.